Rhesus CE expression on patient red blood cells is an independent prognostic factor for adenocarcinoma of the lung. (26th April 2017) - Schulze, A. B.; Schmidt, L. H.; Baie, L.; Heitkötter, B.; Kuemmel, A.; Mohr, M.; Buhl, R.; Hillmann, H.; Geißler, G.; Kelsch, R.; Görlich, D.; Berdel, W. E.; et al.
Abstract: Objectives: The influence of blood group antigens on cancerogenesis is shown for distinct tumor types, yet the impact of Rhesus blood group antigens in lung cancer is not clarified. Materials and Methods: To investigate the impact of Rhesus blood groups a non‐small cell lung cancer (NSCLC) collective (n = 1047) was analyzed retrospectively. Using a second cohort of n = 340 primarily operated stage I‐III NSCLC patients, we evaluated immunohistochemistry of CD47‐antibody stained tissue samples in correlation to histopathologic subtype and Rhesus blood group. Results and Conclusion: In 516 of 1047 patients blood group data were available. Seven different RhCE phenotypes were grouped as "··ee, " "ccE·, " and "C·E·." Adenocarcinoma patients with Rh "··ee" revealed improved overall survival (29 (21.2‐36.8) m; HR 1.00 [index]) compared with Rh "ccE·" (19 (1.9‐36.1) m; HR 1.76 [1.15‐2.70]) and Rh "C·E·" (10 (7.4‐12.6) m; HR 2.65 [1.70‐4.12]) univariately ( P  < .001) and multivariately ( P  < .001). Rh "··ee" showed reduced incidence of CNS‐metastasis ( P  = .014) and metastasis count ( P  = .032) in stage IV adenocarcinoma. Immunohistochemistry associated CD47‐positivity with adenocarcinomas (n = 340, P  = .048). In n = 51 cases blood group data were available. The prognostic effect of Rh "··ee" compared with Rh "ccE·" and Rh "C·E·" was stated ( P  = .001), foremost in CD47‐positive adenocarcinomas (Rh "··ee" vs. Rh "ccE·" and Rh "C·E·, " P  = .008). Inversely Rh "ccE·" or Rh "C·E·" was found beneficial in CD47‐negative non‐adenocarcinomas ( P  = .046). Phenotypic RhCE expression may be an independent prognostic factor for overall survival in adeno‐NSCLC. We hypothesize an erythrocytic‐immunologic interaction with tumor tissue, possibly altered by RhCE and CD47, resulting in a metastatic prone condition.